NEGASI DALAM BAHASA INDONESIA DAN BAHASA INGGRIS - Dian Noviani Syafar (JURNAL ARBITRER, 2016)
This study is entitled Negation in Indonesia and English. Traditionally, people differentiate positive and negative sentences by identifying "not" in Bahasa and "tidak" as negation markers in English. These negation markers can be presented with words, phrases and clauses that form negation sentences in Bahasa Indonesia and English.  This paper tries to describe and compare the other negation markers in these both languages. The data are written and unwritten from that taken from daily conversation.